The Effect of Elderly Exercise on Reducing Blood Pressure in Hypertension Sufferers in North Cimpu Village, Suli District, Luwu Regency in 2025 - A.Wardah Muzfah; Andi Satriana (Professional Evidence-based Research and Advances in Wellness and Treatment, 2025)
Hypertension is a chronic condition commonly experienced by the elderly and poses a significant risk of serious complications if left untreated. One effective non-pharmacological intervention for managing blood pressure is elderly exercise. This study aims to determine the effect of elderly exercise on reducing blood pressure among hypertension patients in North Cimpu Village, Suli District, Luwu Regency, South Sulawesi Province. The research design used a quantitative approach with a quasi-experimental one-group pretest-posttest design. The sample consisted of 21 elderly individuals aged 45 years and over. Data were collected by measuring blood pressure before and after the elderly exercise intervention. Statistical analysis using the Wilcoxon Signed Rank Test showed a significant effect of elderly exercise in lowering both systolic and diastolic blood pressure (p = 0.000). These findings suggest that elderly exercise is an effective strategy for reducing blood pressure and can be recommended as a promotive and preventive effort for managing hypertension in the elderly population.